2013
DOI: 10.1016/j.jsr.2012.10.015
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical factor analysis of a safety culture survey

Abstract: This clarification of the major factors emerging in the measurement of safety cultures should impact the industry through a more accurate description, measurement, and tracking of safety cultures to reduce loss due to injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 61 publications
(107 reference statements)
5
46
0
2
Order By: Relevance
“…On the other hand, the organizational culture analysis methods also ranged from thorough and time-consuming ethnography to simple quantitative questionnaire surveys [19]. The questionnaire has some limitations for capturing every aspect of the safety culture [17], since predicting safety culture in a survey is not easy [20]. However, the questionnaire does show shared attitudes [11].…”
Section: Safety Culture and Safety Climate Assessmentmentioning
confidence: 99%
“…On the other hand, the organizational culture analysis methods also ranged from thorough and time-consuming ethnography to simple quantitative questionnaire surveys [19]. The questionnaire has some limitations for capturing every aspect of the safety culture [17], since predicting safety culture in a survey is not easy [20]. However, the questionnaire does show shared attitudes [11].…”
Section: Safety Culture and Safety Climate Assessmentmentioning
confidence: 99%
“…Previous collaborative research by the authors has shown empirically that many managers have started showing interest in safety performance and their conclusion is that intervention should be directed towards workers and worker behavior [27]; [28]. A safety culture (a sub-unit of organizational culture) does not have a unique and universal definition [4]. However, it can be defined as the product of the individual and group values, attitudes, beliefs, risk-perceptions [29], competencies, norms, principles, and patterns of behavior that determine the commitment of employees to health and safety, as well as the style and proficiency of an organization's health and safety programs [30].…”
Section: Safety Culture and Safety Climatementioning
confidence: 99%
“…Reviews of safety culture surveys identified some common aspects, for instance: management concern and commitment, personal responsibility, peer support for safety, employees' involvement in health and safety activities, and the SMS [4]; [21]; [24]. According to Cooper's model, the concept of safety culture contains three elements, which are related to people, their behavior and their interaction with the safety management system within an organization: internal psychological factors (safety climate), external observable factors -organization (SMS) and job (safety behavior) (see Fig.…”
Section: Model Of Safety Culture and Knowledge Management Aspectsmentioning
confidence: 99%
See 2 more Smart Citations